Governance and Public Leadership: Bundles of Democratic societies? - BC, Basheka (African Journal of Governance and Public Leadership, 2021)
Like an elephant being described by blind men differently depending on where each of them touches, governance and public leadership are concepts prone to different interpretations by different people. Some commentators would even uncourteously question whether a certain theme falls within the scope and intellectual boundaries of Governance and Public Leadership. Yet Governance and Public leadership are themes that have walked the practices and theoretical debates about running of society and ought to have a certain degree of uniformity in their understanding. Governance and leadership have solved problems of mankind but they have also in innumerable ways contributed to creation of problems of mankind. As such, they are concepts whose significance to the management of societal affairs ought to be appreciated and understood. A failure in governance and public leadership affects every person in society.